CPU Bound Analysis of Wordcount Application in Hadoop Yarn Virtualized Nodes Using the Xen Platform - Santos, Marcela; Santos, Katyusco; Alves, Edlane; Dantas, Ana (Anais do Simpósio em Sistemas Computacionais de Alto Desempenho (SSCAD); 2018: Anais do XIX Simpósio em Sistemas Computacionais de Alto Desempenho, 2018)
The following topics are dealt with: parallel processing; cloud computing; power aware computing; multiprocessing systems; graphics processing units; resource allocation; parallel architectures; scheduling; parallel programming; program compilers.